TINGKAT KETERAMPILAN PASSING DAN SHOOTING FUTSAL PADA PEMAIN TIM FUTSAL KOMESRA FC KAB LUWU - Ismail Syamsuddin; Nurjamal Nurjamal; Mutmainnah Mutmainnah (Program Studi Ilmu Keolahragaan FIK UNM, 2022)
The formulation of the problem in this study is How to Survey Passing and Shooting Futsal Skills on Komesra FC Futsal Team Players Luwu Regency. The type of research that will be used in this study is quantitative descriptive analysis. into one whole sample. While data analysis using SPSS 21 using descriptive test, and normality test. Based on the results of the analysis of the Futsal Passing and Shooting Skills Survey on the Komesra FC Luwu Regency Futsal Team Players, the percentage value of the Luwu District Komesra FC futsal players' passing skills is in the good category with a total percentage of 53% of the sample or 8 people are in the good category after doing passing test with a distance of 9 meters. Meanwhile, the results of the shooting skills of the Futsal Komesra FC players in Luwu Regency are in the sufficient category with a total percentage of 53% or 8 people are in the sufficient category after taking a shooting test with a distance of 8 meters.